2002
DOI: 10.1016/s0735-1097(02)01738-2
|View full text |Cite
|
Sign up to set email alerts
|

Improved myocardial ischemia/reperfusion injury in mice lacking tumor necrosis factor-α

Abstract: Tumor necrosis factor-alpha exacerbates myocardial I/R injury at an early stage of reperfusion by activating NF-kappaB, thereby inducing chemokines and adhesion molecules and facilitating leukocyte infiltration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
107
0
4

Year Published

2003
2003
2015
2015

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 184 publications
(116 citation statements)
references
References 21 publications
5
107
0
4
Order By: Relevance
“…Sun and coworkers demonstrated that TNF-α null mice were protected from cardiac rupture and chronic dysfunction following infarction, and exhibited suppressed inflammation and attenuated MMP activity in comparison with wildtype animals [151]. Several other investigations have suggested an essential role for TNF-α in mediating inflammatory injury following infarction [152], [145]. Inhibition studies have produced contradictory findings regarding the effects of TNF-α neutralization on the infarcted heart.…”
Section: Tnf-αmentioning
confidence: 99%
“…Sun and coworkers demonstrated that TNF-α null mice were protected from cardiac rupture and chronic dysfunction following infarction, and exhibited suppressed inflammation and attenuated MMP activity in comparison with wildtype animals [151]. Several other investigations have suggested an essential role for TNF-α in mediating inflammatory injury following infarction [152], [145]. Inhibition studies have produced contradictory findings regarding the effects of TNF-α neutralization on the infarcted heart.…”
Section: Tnf-αmentioning
confidence: 99%
“…1). Because IL-1␤ and TNF-␣ are B-responsive proinflammatory cytokines and play an important role in myocardial inflammation and injury (34,35), we then explored the effects of IL-18 on IL-1␤ and TNF-␣ expression and determined whether IL-18 induces cytokine expression via NF-B activation. Fig.…”
Section: Il-18 Increases Nf-b Dna Binding Activity and Induces B-drivmentioning
confidence: 99%
“…23 On the basis of those results, we presumed that the TNF--induced upregulation of ICAM-1 plays an important role as an initial process of TNF--related cardiac injury. In a TNF-KO mouse model of ischemia -reperfusion reduction of nuclear-factor-kappa activation and ICAM-1 mRNA expression has been shown, 15 but in a permanent occlusion model of MI, no studies have elucidated the involvement of ICAM-1 and cellular infiltration in the inhibition of TNF-.…”
mentioning
confidence: 99%